Influence of La on reduction behaviour and Ni metal surface area of Ni–Al2O3 catalysts for COx free H2 by catalytic decomposition of methane. (9th March 2015) - Anjaneyulu, Ch.; Naveen Kumar, S.; Vijay Kumar, V.; Naresh, G.; Bhargava, S.K.; Chary, K.V.R.; Venugopal, A.
Abstract A series of Ni:Al:La mixed oxides derived from hydrotalcite precursors with varying La/Al mole ratio were examined for COx free H2 production by catalytic decomposition of CH4. The physico-chemical characteristics of Ni:Al:La were determined by XRD, UV-DRS, SEM, TEM, Raman spectroscopy, BET-surface area, TPR and O2 pulse chemisorption measurements. Addition of La to Ni–Al improved the Ni metal surface area and the reduction behaviour of NiO particles is dramatically changed. Particle size of Ni was similar to the size of carbon nano fibre in the deactivated catalyst. A direct correlation between Ni metal surface area and the CH4 decomposition activity was observed.